In Vitro Test of Leilem Leaf Ethanol Activity on β-Glucosidase Enzyme Inhibition - Krispela Trifosa Oktavia Siregar; Fona Dwiana Hermina Budiarso; Billy Johnson Kepel; Fatimawali Fatimawali; Aaltje Ellen Manampiring; Widdhi Bodhi (Sam Ratulangi University, 2024)
Diabetes is a chronic metabolic disease with signs of elevated blood glucose levels. One of the targets of antidiabetic drugs is to inhibit the enzyme α-/β-glucosidase which works in the process of glucose absorption. Leilem plant (Clerodendrum minahassae Teisjm. & Binn.) is well known and used as a dish and medicine for several diseases in Minahasa and has potential as an antidiabetic agent. This study aimed to determine the activity of ethanolic extract of leilem leaves in inhibiting β-glucosidase enzyme. The extract was prepared with 96% ethanol. Antidiabetic properties were measured by β-glucosidase enzyme inhibitory activity. The inhibitory concentration (IC50) values of the extract compared tp acarbose were 28,229 and 13,716. Ethanol extract of leilem leaves inhibits β-glucosidase enzyme. Keywords : β-glucosidase; ethanol extract; in vitro; leilem leaf